A new single-view 3D pantograph reconstruction aided by prior CAD model. (August 2021) - Sun, Tiecheng; Liu, Guanghui; Peng, Jianping; Meng, Fanman; Liu, Shuaicheng; Zhu, Shuyuan
Abstract: This paper proposes a novel 3D pantograph reconstruction method for the visualization and inspection based on the single-view scanned data and prior Computer-Aided Design (CAD) model. The proposed method uses the point cloud to reconstruct a scanned surface by the fusion of the point cloud and prior CAD surface. Then, a 3D model is reconstructed by integrating the scanned surface and the CAD model through an edge reconstruction process. Finally, the pantograph is inspected by the deviation analysis. The proposed method is validated by the pantograph data collected in a locomotive workshop with line structured light scanning measurement technology. Compared with the state-of-the-art methods, the proposed method can reconstruct the complete 3D model with high accuracy. Furthermore, the reconstructed 3D model has been successfully applied to the anomaly detection and visualization in the pantograph inspection, which is of great significance for improving the pantograph inspection efficiency and reducing traffic accidents. Highlights: A 3D pantograph reconstruction method is proposed for visualization and inspection. A non-hole surface reconstruction method is proposed based on CAD mesh densification. The 3D visualization can improve the efficiency of the pantograph maintenance.